The mediating role of destination satisfaction between the perception of gastronomy tourism and consumer behavior during COVID-19 - Durmaz, Yakup; Cayiragasi, Filiz; Copuroglu, Filiz (ELSEVIER)
This study aims to examine how covid-19 affect consumer behaviors within gastronomy tourism and the mediating role of destination satisfaction in this relationship. The research data was collected from 812 con -sumers through questionnaires. The collected data was analyzed through IBM SPSS 25 (Hayes, 2009) and PROCESS v3.4 macro. The study found that the perception of gastronomy tourism has a positive and significant effect on destination satisfaction and consumer behavior and that destination satisfaction has a positive and significant effect on consumer behavior. It was also found that destination satisfaction has a partial mediating role between the perception of gastronomy tourism and consumer behavior. Due to social distancing, the pandemic has greatly affected the interest in gastronomy tourism. The fact that people avoid eating in crowded places has led to a decrease in the interest in gastronomy tourism. As destination satisfaction has a mediating effect between gastronomy tourism and consumer behavior, more emphasis should be put on destination satisfaction in the field of gastronomy tourism. This study answers the critical question of how gastronomy tourism affects consumer behavior and reveals the role of destination satisfaction in this relationship.
Keywords: Destination satisfaction; Gastronomy tourism; Consumer behavior; Consumer behavior